Near-field plume properties of an ion beam formed by alternating extraction and acceleration of oppositely charged ions. (25th August 2016) - Oudini, N; Aanesland, A; Chabert, P; Lounes-Mahloul, S; Bendib, A
Abstract: This paper is devoted to study the expansion of a beam composed of packets of positively and negatively charged ions generated by alternating extraction and acceleration. This beam is extracted from an ion–ion plasma, i.e. the electron density is negligible compared to the negative ion density. The alternating acceleration of ions is ensured by two grids placed in the ion–ion plasma region. The screen grid in contact with the plasma is biased with a square voltage waveform while the acceleration grid is grounded. A two-dimensional particle-in-cell (2D-PIC) code and an analytical model are used to study the properties of the near-field plume downstream of the acceleration grid. It is shown that the possible operating bias frequency is delimited by an upper limit and a lower one that are in the low MHz range. The simulations show that alternating acceleration with bias frequencies close to the upper frequency limit for the system can achieve high ion exhaust velocities, similar to traditional gridded ion thrusters, and with lower beam divergence than in classical systems. Indeed, ion–ion beam envelope might be reduced to 15° with 70% of ion flux contained within an angle of 3°. Thus, this alternating acceleration method is promising for electric space propulsion.